The Combined Effects of Road Salt and Biotic Stressors on Amphibian Sex Ratios. (17th December 2020) - Leggett, Sagan; Borrelli, Jonathan; Jones, Devin K.; Relyea, Rick
Abstract: Aquatic systems worldwide are threatened by the anthropogenic use of synthetic chemicals, including pesticides, pharmaceuticals, and road de‐icers. Exposure to contaminants can alter the behavior, morphology, and physiology of organisms if it occurs during sensitive life stages. For instance, past studies have documented feminization of male amphibians following herbicide exposure and skewed sex ratios among amphibian populations exposed to road salt. However, many of these studies lack the complexities found within natural environments, such as competition with conspecifics or threat of predation, which are also known to influence development. Thus, it is important to understand how anthropogenic and natural stressors interact to alter animal sex ratios. Given the growing concern of secondary salinization of freshwater systems, we exposed larval wood frogs ( Rana sylvatica ) to either road salt (sodium chloride [NaCl]) or an alternative salt mixture (NaCl, magnesium chloride [MgCl2 ], and potassium chloride [KCl]) at 3 concentrations (200, 600, and 1000 mg Cl − /L) crossed with 3 biotic stressors (no‐stressor control, competition, or predator cues) to examine their potentially interactive effects on sex . Exposure to biotic stressors and NaCl did not influence wood frog sex ratios. In contrast, tadpole exposure to the intermediate salt mixture concentration significantly reduced the proportion of female frogs. Future studies are needed to determine whether such changes in sex are widespread among sensitive species with complex life cycles, and to assess the consequences of sex ratio changes on long‐term population dynamics. Environ Toxicol Chem 2021;40:231–235. © 2020 SETAC